Maria Kalaw Katigbak a charmed life - Mercado, Monina A. (Monina Allarey) (Anvil, 2007)
"...the moment [Maria] took the spotlight as senator-elect in a clean Liberal Party sweep with President Diosdado Macapagal, we always knew that one day a Maria Kalaw Katigbak biography had to be written. It is one of those inevitable fruitions of a life laden with a noble genealogy, beauty, intellectual prowess, and a charmed destiny." - Puri K. Katigbak, Prologue.